The results of cooperation between FSBSI “ARC “Donskoy” and FSBSI “NCG named after P.P. Lukiyanenko” in winter barley breeding - E. G. Filippov; A. A. Dontsova; D. P. Dontsov; V. V. Nesterenko; N. V. Serkin; Т. Е. Kuznetsova (Зерновое хозяйство России)
Barley is the main grain feed crop in the Russian Federation. In the Southern Federal District, winter barley breeding tends to be carried out in the Rostov Region and Krasnodar Area. The current paper has presented the results of joint work on winter barley breeding of the FSBSI “Agricultural Research Center “Donskoy” and the FSBSI “National Center of Grain named after P. P. Lukiya-nenko”. The purpose of the study was to develop winter barley varieties using the initial material of local and Krasnodar breeding. The varieties developed by scientists from these research institutions occupy a leading place in the structure of sown areas in the south of the country. The Zernograd scientists' participation in the hybridization of Krasnodar varieties has resulted in the development of the varieties “Rostovsky 55”, “Timofey”, “Erema”, “Vivat”, “Foks 1”. In 2016 a new facultative barley variety “Marusya” was sent to the State Variety Testing. For the scientists of the National Center of Grain named after P. P. Lukiyanenko the varieties of “Donskoy”, which have been bred in a more northern region, are of certain interest, since they have a fairly high level of frost and winter tolerance and other traits of adaptability. Thus, the variety “Larets”, developed by the ARC “Donskoy” was included in the program for deepening the tillering node by the Krasnodar breeders.